Soil Fertility Appraisal under Dominant Land Use Systems in North-Eastern Part of Arid Rajasthan - Kumar, Mahesh; Raina, P; Sharma, B K (Annals of Arid Zone, 2016)
Surface soil samples (0-30 cm depth) in north-eastern part of arid Rajasthan from agriculture (rainfed and irrigated), grazing lands (orans) and sand dunes were collected, analyzed and categorized for fertility status. The pH and EC values of the soils ranged from 7.7 to 9.6 and 0.02 to 2.5 dS m-1, respectively. The average organic carbon (OC) content in the soils varied from 0.30 to 6.20 g kg-1 with the lowest content in sand dunes (0.07 g kg-1). Whereas, soils under rainfed crops and grazing lands had 1.3 and 1.5 g kg-1 OC, respectively. Soils under irrigated crops recorded highest values for OC (2.2 g kg-1). Phosphorus deficiency was spread all over the district. The available potassium content varied from 84 to 551 kg ha-1 with a mean values of 212, 161 and 156 kg ha-1 in soils under grazing lands, agriculture (irrigated & rainfed crops) and sand dunes, respectively. Deficiency of potassium (<130 kg ha-1) was more pronounced under agriculture than the grazing lands. Soils of the district were adequate in available iron (4.2-30.4 mg kg-1), manganese (5.5-40.5 mg kg-1) and copper (0.22-7.4 mg kg-1). However, zinc content in the soils varied from 0.28 to 5.90 mg kg-1 and about 30% of the samples were found deficient. Zinc deficiency was wide-spread both under rainfed and irrigated agriculture. A significant and positive correlation was observed between OC and P, K, Fe, Mn and Zn. However, the available nutrients (P, Fe, Zn and Cu) showed a negative correlation with pH and CaCO3. Key words: Soil fertility, land use systems, micronutrients, organic carbon, arid Rajasthan.